Pendampingan Kemandirian Ekonomi Berbasis Keuangan Syariah Untuk Mewujudkan Kesetaraan Ekonomi Masyarakat Di Dusun Kwangenrejo Desa Leran Kecamatan Kalitidu Kabupaten Bojonegoro Jawa Timur - Hamdani, Hamdani (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service activity aims to provide assistance and economic empowerment to the community in fulfilling sustainable economic improvement in Kwangenrejo Hamlet, Leran Village, District. Kalitidu District. Bojonegoro, East Java. In carrying out community service, we use the Asset Based Community Development (ABCD) method, namely with five stages of discovery, dream, design, define and destiny. The results of this service activity were found to be (1) improving the community's economy, especially the livestock community, the majority of which are farmers and rice paddy cultivators with the rolling goat program. (2) The provision of working capital loans by BMT Nurul Ummah Ngasem is an indicator of economic empowerment activities in improving the economy of village communities. Based on observations, there is economic improvement and economic equality between the Muslim community and the Catholic community after the empowerment of rolling goats and working capital